Jeunesse de papier - Larochelle, Catherine; et al. (2021)
Projet d’histoire publique réalisé dans le cadre du cours HST6406 Histoire de l’enfance : Jeunesse de papier, une analyse de revues jeunesse québécoises des années 1950 et 1960.

Feminising the ‘Modern’ Sweetness: Gender and Western-Style Confectionery in Interwar Japan - Tsay, Lillian (Gender & History, 2022)
This article explores how the feminisation of Western-style confectionery was critical in bridging sweetness with modernity in interwar Japan. By examining three categories of Japanese women – the ‘female worker’, the ‘modern girl’ and the ‘good wife, wise mother’, it argues that the sweetness of Western-style confectionery was associated with the female body due to women's extensive involvement in the production process and performances in visual advertisements. As these women helped construct the cultural imagination of Western-style confectionery as a feminised product, their presence also unfolds the key links between Japan's rising consumer culture and the empire's growing power.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1468-0424.12657

« Fanm toujou viktim » : Regards sur la violence sexualisée et les expériences genrées pendant la dictature duvaliériste à travers deux entretiens oraux - Belony, Lyns-Virginie (Revue d'histoire de l'Université de Sherbrooke, 2022)
Découlant des retombées de notre thèse de doctorat et à travers l’analyse de deux entretiens oraux (issus d’un corpus plus ample de 47 entretiens réalisés entre 2018 et 2021 avec des Haïtiens installés au Québec), nous voulons ici réfléchir à la manière dont les expériences des femmes sous les Duvalier furent appréhendées par les participants à notre étude, notamment en ce qui concerne l’enjeu des violences sexualisées et des rôles de genre. S’il reste encore à écrire sur la complexité des expériences des femmes pendant cette période, notre propre ébauche démontre comment ce silence presque institutionnalisé sur la dictature et le tabou relatif à toutes discussions sur les violences sexualisées nuisent à une appréciation plus complète et raffinée de l’ampleur même de la violence duvaliériste.

Vaccination des enfants dans les quartiers marginalisés : défis liés à l’équité et à la diversité dans le cadre des campagnes de vaccination contre la COVID-19 - Rousseau, Cécile; Quach, Caroline; Dubé, Ève; Vanier-Clément, Anabelle; Santavicca, Tara; Monnais-Rousselots, Laurence (Relevé des maladies transmissibles au Canada, 2022)
Number: 10
Keywords: =CL

Vaccination of children in marginalized neighbourhoods: Equity and diversity challenges with COVID-19 vaccination campaigns - Rousseau, Cécile; Quach, Caroline; Dubé, Ève; Vanier-Clément, Anabelle; Santavicca, Tara; Monnais-Rousselots, Laurence (Canada Communicable Disease Report, 2022)
Number: 10
Keywords: =CL

Letter to the Editor: “COP26: what is the message for public health?” Response from the Université de Montréal One Health initiative - Aenishaenslin, Cécile; Batal, Malek; Boiteux, Manon; Externe, Lien vers un site; Fenêtre, Celui-Ci S'Ouvrira Dans Une Nouvelle; Bouchard, Michèle; Brun, Yves; Brodeur, Jacques; Carabin, Hélène; Carrier, Julie; Kasisi, Robert; Kritikou, Ekat; et al. (Canadian Journal of Public Health, 2022)
Number: 5 Num Pages: 788-789 Pages: 788-789 Place: Ottawa, Netherlands Volume: 113
Keywords: =CL; Physical Fitness And Hygiene; Public Health And Safety; Public health

Pandémie de rougeole, 1988-1992 : virus, vaccinations de masse et vulnérabilités contemporaines - Monnais, Laurence (Anthropologie et Sociétés, 2022)
At the turn of the 1990s, measles swept the world. Vaccine-preventable since 1963, the “first disease” is nevertheless one of the great absentees of a pandemic century that is slow to come to an end, if not to make it the incarnation of a rampant anti-vaccinationism. Through a chronicle of the “crisis” of 1988‑1992, we will return to the process of coproduction between the infection and the technologies that protect against it. In particular, we will address the social dimension of the viral infection in order to understand why mass vaccination, at the heart of a strong eradication effort, is not enough to prevent measles and even contributes to increasing health inequalities that influence its epidemiology in return. The COVID‑19 experience urges us to conduct this kind of retrospective work and to mobilize history as a discipline of public health to better understand the place of vaccination in the viral and contagious past and present. WHO documentation, scientific literature and ethnographic fieldwork will together force an “equal” approach to the spaces and actors involved, bringing together very local experiences and international policies to reveal the pitfalls of an ultra-technologized and very vertical global (public) health.
Number: 3
Keywords: =CL; Monnais; OMS; WHO; desigualdades; enfermedad social; eradication; erradicación; immunizations; inequities; iniquités; maladie sociale; measles; pandemia; pandemic; pandémie; rougeole; sarampión; social disease; vaccinations; vaccines; vaccins; vacunaciones; vacunas; éradication

Femmes en guerre de l’époque médiévale à nos jours. Introduction - Handfield, Nicolas; Le Gac, Julie; Poitras-Raymond, Chloé (Femmes en guerre : De l’époque médiévale à nos jours, 2022)
Code: Femmes en guerre : De l’époque médiévale à nos jours

Se remémorer la guerre : la place de la violence sexuelle dans les souvenirs des vétérans britanniques de la Seconde Guerre mondiale - Poitras-Raymond, Chloé (Cahiers d'histoire, 2022)
À la fin de la Seconde Guerre mondiale, les femmes allemandes ont subi des crimes de violence sexuelle perpétrés par les troupes alliées. Les vétérans britanniques ayant participé aux opérations militaires et à l’occupation de l’Allemagne gardent des souvenirs marquants de ces crimes et des victimes allemandes. L’analyse de leurs témoignages écrits et oraux, diffusés entre 1980 et 2010, démontre que les vétérans britanniques construisent le récit mémoriel de leur expérience de guerre d’une façon qui leur permet non seulement de préserver leur propre réputation, mais également celle de l’armée. Ils mobilisent ainsi plusieurs processus narratifs pour assurer une image positive du groupe auquel ils appartiennent. Cela se traduit notamment par une tentative de se présenter en héros sauveurs des victimes allemandes agressées par les autres Alliés et par une volonté de démontrer au public que les soldats britanniques ne se livraient pas à ce type de crime. En se distanciant des actes commis par les autres Alliés, les vétérans britanniques cherchent ainsi à présenter leur armée comme une institution disciplinée.

Les enseignantes et enseignants contractuels dans l’université du XXIe siècle - Séguin, Michaël; Guay, Françoise; Boucher, Marie-Pierre; Lewis, David Lionel; Héon-Morissette, Barah (ACFAS, 2022)
Ces actes sont le fruit d’une réflexion entreprise il y a plus de trois ans par un collectif de chargées et chargés de cours de Montréal et de l’Outaouais, réflexion qui s’est soldée par un colloque intitulé Subalternité et agentivité : les enseignantes et enseignants contractuels au sein des universités du XXIe siècle. L’intention des initiatrices et initiateurs était d’aborder la situation des personnes chargées de cours de l’intérieur, et bien que nous soyons arrivés à la conclusion que le concept de subalternité rendait difficilement compte de l’agentivité de celles-ci, nous n’en appelons pas moins à un renouveau du cadre et des outils d’analyse. Nos actes sont le reflet d’une réflexion en cours, à la fois foisonnante, complexe et critique, sur la place grandissante, mais toujours marginale, des personnes chargées de cours dans nos universités. Après une première partie dressant un portrait général des emplois contractuels dans l’économie du savoir, notamment dans le monde universitaire, la deuxième aborde plus spécifiquement le quotidien des chargées et chargés de cours. Une troisième traite des concepts servant à décrire cette réalité, alors que la dernière offre une synthèse du panel de clôture, une conclusion en forme de manifeste, ainsi qu’un hommage au collègue Michel Sarra-Bournet, à qui est dédié ce cahier. C’est là, à notre connaissance, le premier ouvrage collectif et scientifique traitant de la réalité des chargées et chargés de cours au Québec et au Canada – et qui plus est, il le fait à partir du point de vue des actrices et acteurs concernés.

Petit traité de conceptologie zen - Lewis, David Lionel (PREMIO : excellence ; no. 9, Collection Hors-série, 2022)
Accepted: 2022-08-03T12:00:25Z

Le concept de「ma」et l’identité nationale japonaise - Lewis, David Lionel (Université de Montréal, 2022)
Le 「ma」 est, depuis quelques décennies, un concept dont il est assez souvent question dans les textes portant sur le Japon. Tel le kanji qui le représente, soit un pictogramme qui montre le soleil qui perce entre les deux battants d’une porte, le 「ma」 exprime un entre-deux dynamique et porteur de sens. Après un premier chapitre qui explore les liens entre langue et culture au Japon, quatre chapitres sont consacrés au 「ma」, un premier qui présente un état des lieux, un second qui explore ses précurseurs ainsi que ses formes disciplinaires, sauf en musique et en architecture, traités au chapitre suivant, alors que le dernier chapitre tente de cerner et de définir le 「ma」, et qu’une annexe survole ce qu’il en est en Occident. Le sixième chapitre de la thèse présente la dichotomie 「内・外 uchi-soto」, marqueur premier de l’appartenance à tout groupe au Japon, incluant la nation. Suit un chapitre portant sur la frontière entre le uchi et le soto de la nation japonaise, puis un autre qui explore les formes que prend l’identité nationale japonaise. Le dernier chapitre offre une synthèse. Il en ressort que : - le 「ma」 est un concept associé à un terme importé au début de l’âge classique, mais ce n’est qu’à la transition entre le 戦国 sengoku (mi 15e à fin 16e) et l’ère 江戸時代 Edo (1600-1868) que les conditions seront réunies pour permettre la naissance du concept. Celui-ci restera toutefois presque purement disciplinaire jusqu’à 昭和 Shōwa (1926-1989), après quoi il prendra des formes qu’on peut qualifier d’identitaires, d’abord en opposition à l’Occident au début Shōwa, puis comme ambassadeur d’une identité japonaise consolidée à partir des années 1960.
Accepted: 2022-04-04T14:38:42Z

Travailleuses anonymes et modernité énergétique. L’industrie électrique et gazière et l’économie domestique à Montréal, 1904-1959 - Hatton-Proulx, Clarence (Revue d’histoire de l’Amérique française, 2022)
Cet article analyse le rôle important joué par les femmes dans le processus de transition énergétique vers des sources d’énergie distribuées par des réseaux universels et invisibles (le gaz et l’électricité). En considérant le cas de Montréal durant la première moitié du 20e siècle, il démontre leur triple rôle dans ce processus. Premièrement, à travers l’histoire de l’École ménagère provinciale de Montréal, l’article présente le développement de la discipline de l’économie domestique et ses liens avec l’industrie de l’énergie montréalaise. Deuxièmement, il analyse la promotion de l’électricité et du gaz par les vendeuses formées en économie domestique de la compagnie monopolistique Montreal Light, Heat & Power. Troisièmement, il se penche sur l’influence des savoirs issus des sciences domestiques sur les standards de confort et les pratiques de consommation d’énergie.

Opposing Urban Energy Landscapes: Petitions and Letters against Coal Yards, Wood Yards, and Gas Stations in Montréal (1940s-1960s) - Hatton-Proulx, Clarence (The Metropole, 2022)
Editor’s note: This is the second post in our theme for January 2022, Urban Environmentalism. Additional entries can be seen at the end of this article. By Clarence Hatton Throughout the twen…

Judaïsme, islam et modernités - Rabkin, Yakov M. (Éditions i, 2022)
Fruit de plusieurs années de travail et d’échanges, ce recueil est un ouvrage inédit de Yakov Rabkin. Auteur d’audience internationale et historien des sciences renommé, il y réunit une synthèse de ses travaux sur le judaïsme agrémenté de récits de ses voyages et rencontres en Asie et en Afrique. En tant que tel, il constitue un ouvrage de première importance aussi bien en ce qui concerne la spiritualité judaïque que son histoire contemporaine. Le résultat en est un texte qui peut intéresser aussi bien les savants que tout un chacun. Il souligne au fil de ses chapitres les points d’unité entre les religions monothéistes, rappelant que les valeurs traditionnelles essentielles du judaïsme sont proches de celles de l’islam. Ce livre s’articule en trois parties : une première constituant une introduction au judaïsme et quelques thèmes reliés à l’éthique tels que la honte ou le pardon, une seconde sur les relations entre judaïsme et l’islam et une troisième sur les relations du judaïsme avec la modernité, que ce soit scientifique ou politique. Les études qui composent le présent recueil développent une approche historique qui se garde de la polémique. Son analyse met en relief l’instrumentalisation de l’histoire à des finalités politiques dans le prolongement de son essai précédent, Au nom de la Torah. Comme dans tous les ouvrages essentiels, l’ensemble révèle à chaque page de nouveaux prolongements. Chaque chapitre est une invitation à approfondir son approche et affiner son regard dans une ouverture intellectuelle enrichissante et stimulante. Ce livre ouvre une perspective d’échanges, de dialogue et de tolérance avec l’autre, qu’on partage ou non ses idées ou ses croyances. Ce qui n’est pas la moindre des utilités de ce livre.
Préface de Shlomo Sand.

Les relations transdétroits sous le règne de l’empereur Kangxi : son rôle intégrant dans la première ouverture au commerce maritime chinoise - Fu, Nanxin (89e Congrès de l'Acfas, 2022)
Aujourd’hui, si les circonstances du détroit de Taiwan jouent un rôle à la fois important et délicat dans les relations extérieures de la Chine, elles ont en effet exercé une influence remarquable très tôt sur les premiers essais d’ouverture maritime sous la dynastie des Qing (1644-1911) vers la fin du XVIIe siècle. En nous appuyant principalement sur les Annales véridiques de la dynastie Qing (Qing shilu) et d’autres documents officiels de la Cour impériale, nous nous proposons de traiter dans cette communication les « relations transdétroit » vers la fin du XVIIe siècle sous le règne de l’empereur Kangxi. Bien que cette page historique soit courte et loin au regard des enjeux politiques, sociaux et identitaires contemporains de cette région, nous espérons ramener le passé au présent pour caractériser le rôle des rapports interdétroits dans la politique extérieure du gouvernement central dans l’Ancien Régime et de nos jours d’une part, ainsi que pour comprendre le principe des stratégies maritimes chinoises à travers le détroit ainsi que dans l’Asie- Pacifique d’autre part.

Una gatta da pelare : vies publiques et vies privées des Italiennes récemment arrivées à Montréal - Vigliano, Chiara (Université de Montréal, 2022)
This doctoral dissertation focuses on a contemporary phenomenon that has been understudied until now: the recent migration of highly educated, professional, and academic women. This profile corresponds to that of a significant proportion of Italian women who, since the 1990s, have left their country for large European cities or the North American continent. This movement intensified in the 2000s and, even more so after the financial crisis of 2008. This study is based on a qualitative analysis of the migration experience of 32 Italian women, aged 25 to 65, all with a university degree, who arrived in Montreal between 1990 and 2016. The study is in line with North American and European scientific literature on oral history, the history of migration and the new perspectives brought by its encounter with the history of women and gender. The aim is to take a critical look at this contemporary Italian female mobility that is educated and qualified. Thirty-two semi-directed interviews allowed us to explore in depth this recent migratory phenomenon and to grasp the meaning of this feminine experience, the attitude of these Italian women towards the status of women and feminism, in Italy and in Quebec, the existential choices that this migratory experience has demanded of them as women and intellectuals, in their private and public lives, and the possible changes that have resulted in terms of identity, religion and ideology. The objective is to define the socio-cultural profile of these women, their geographical, social and cultural origins, their educational and professional background in Italy and in the context of migration, and to explore the reasons that led them to leave Italy and choose Montreal. It also examines the complex migratory paths of these Italian women, the main challenges they have faced, and interprets these issues in their respective departure and arrival contexts. Migration and institutional policies, women’s status and reforms, unemployment and employment opportunities, access to education and academic careers in both countries are the main themes explored in this study. The analysis of the interviews allows us to verify to what extent and in what ways these thirty-two public and private stories reflect the migratory movements of our time. It also enables us to contrast the mobility of these migrant women with that of the Italian women who preceded them in Canada and Quebec, in the very different socio-economic contexts that marked the end of the 20th century and the 21st century. Thus, the globalization of the economy and the advent of digital media, to name but two examples, have generated new forms of identity, mixed, fluid and fragmented, by putting in direct communication these two worlds, the one of departure and the one of arrival, which were previously much more distant. Most of the women in my focus group are from northern Italy, belong to the lower or middle bourgeoisie, and have a high level of education. The political, economic, and cultural climate of the country encouraged them to leave; the many opportunities for education and employment, a better quality of life, and respect for human rights made them choose Montreal. Complex itineraries, fortuitous encounters, both professional and sentimental, and the fundamental role played by profession and career are some of the characteristics of this recent female migration. Suggestions for further research and new themes to explore complete this work.
Keywords: Entrevues et mémoire; Femmes et genre; Histoire; History; History / Histoire (UMI : 0578); Interviews and memory; Italie; Italy; Migration; Public-private; Public-privé; Quebec and Montreal; Québec et Montréal; Women and gender; XIX-XXI centuries; XIX-XXI siècles

Les nobles canadiens après la Cession. Se réinventer pour continuer à exister (1774-1815) - Zissis, Marie (Université de Montréal, 2022)
Entre 1774 et 1815, la noblesse canadienne tente de stabiliser sa position sociale au sein d’une société canadienne désormais sous tutelle britannique. Pour cela, les nobles opèrent une redéfinition culturelle et sociale de leur idée de noblesse afin de s’adapter au nouveau régime. Grâce aux relations qui s’établissent entre les nobles restés dans l’Empire britannique, ceux l’ayant quitté et les nouvelles élites qui s’établissent dans la colonie au tournant du XIXe siècle, il est possible de mieux appréhender la façon dont la noblesse réinvestit son capital symbolique. L’étude des patrimoines matériels, sociaux et intellectuels ainsi que leurs modes de transmission permettent d’examiner les modalités d’adaptation de la communauté noble. Enfin, cette noblesse à cheval entre deux empires, dont les réseaux s’étendent sur de nombreux territoires, permet de mieux percevoir les évolutions qui s’opèrent à cette époque dans les sociétés coloniales et en particulier en Amérique du Nord et au Canada. En étudiant cinq familles emblématiques de la noblesse canadienne, cette thèse tente de répondre à la problématique et aux sous-questions suivantes : comment la noblesse francophone se renouvelle-t-elle et évolue-t-elle en tant que groupe social distinct au sein des élites impériales entre 1774 et 1815 ? Qui est noble ? Être un noble canadien après la Cession dans les empires français et britanniques, qu’est-ce que ça signifie ? Quelles sont les stratégies d’adaptation de la génération de la noblesse canadienne qui vit sa vie publique et adulte entre 1774 et 1815 ? Y a-t-il une « canadianisation » de la noblesse et, si oui, comment se caractérise-t-elle ? Les nobles canadiens s’adaptent-ils au nouveau régime ? Les élites influencent de façon importante la construction de la société dans laquelle elles évoluent : au XIXe siècle la société canadienne-française telle qu’on la connaît jusqu’au milieu du XXe siècle commence à se développer ; elle a en parti été mise en place par et pour les nobles canadiens. Ma recherche a donc pour but de trouver les mécanismes de reproduction des élites coloniales. C’est-à-dire de comprendre comment, en particulier, les nobles continuent à exister sous le Régime britannique. Mon hypothèse est que les nobles réussissent à trouver une forme d’équilibre entre le besoin de renouvellement qui découle du changement de régime et leur fidélité à des traditions présentées comme séculaires. Ce sont des « caméléons sociaux » qui existent à travers trois paradoxes : un imaginaire transnational dans une réalité juridique nationale ; un désir d’éternité couplé à un besoin d’évolution constant ; une culture de la distinction affirmée à l’intérieur de frontières poreuses. La thèse cherche encore à mieux comprendre comment se vit une identité transatlantique et coloniale, se détachant progressivement, mais jamais totalement des pairs de la « vieille Europe » et à travers la formation d’une identité américaine au sein des empires. Elle démontre également l’ambiguïté qui existe entre l’identité noble coloniale, qui pousse au détachement par rapport à la métropole, et l’identité élitaire, qui, au contraire, ramène les nobles canadiens vers l’Europe et les caractéristiques de son élite. Between 1774 and 1815, Canadian nobility attempted to stabilize their social position within a Canadian society now under British reign. In that order, nobles operated a cultural and social redefinition of their idea of nobility to adapt to the new regime. Thanks to the relationships that nobles who remained in the British Empire developed with those who left it, and the new elites who settled in the colony, it is possible to better understand how Canadian nobility reinvested its symbolic capital. The study of material, social and intellectual heritages as well as transmission mode make possible to examine the modalities of adaptation of the noble community. Finally, this nobility straddling two empires, whose networks spanned many territories, allows us to better perceive the changes that took place at that time in colonial societies and, more specifically, in North America and Canada. By studying five emblematic families of the Canadian nobility, this thesis attempts to answer the following problematic and sub-questions: how the French-speaking nobility is renewing itself and evolving as a distinct social group within the imperial elites between 1774 and 1815? Who is noble? What does it mean to be a Canadian nobleman after the Conquest in both French and British Empires? What are the coping strategies of the generation of Canadian nobility who lived their public and adult life between 1774 and 1815? Is there a “Canadianization” of the nobility and, if so, how is it characterized? Are nanadian nobles adjusting to the new regime? The elites significantly influence the construction of the society in which they operate: in the 19th century French Canadian society as we know it until the middle of the 20th century began to develop; it was in part set up by, and for, Canadian nobility. My research therefore aims to find its reproduction mechanisms. That is, to understand how, in particular, nobles continued to exist under British rule. My hypothesis is that the nobility manages to find some kind of balance between the need for renewal that arises from regime change and its loyalty to traditions presented as secular. Noblemen and women are “social chameleons” that exist through three paradoxes: a transnational imaginary in a national legal reality; a desire for eternity coupled with a constant need for evolution; a culture of distinction asserted within porous borders. This thesis seeks to better understand how a transatlantic and colonial identity is experienced, separating itself gradually, but never completely from the peers of "old Europe" and through the formation of a North American identity within the empires. It also demonstrates the ambiguity that exists between the noble colonial identity, which encourages detachment from the metropolis, and the elite identity, which, on the contrary, brings the Canadian nobles back to Europe and the characteristics of its elite.
Keywords: =CL; British Empire; Canada; Canadian history / Histoire du Canada (UMI : 0334); Cession; Colonial nobility; Conquest; Empire Britannique; Empire Français; French Empire; Noblesse coloniale

L’internationalisme socialiste français et allemand devant la montée de l’impérialisme (1896-1912) - Soucy, Louis-Félix (Université de Montréal, 2022)
The rise of the European socialist movement under the leadership of the Second International at the turn of the century and its breakup with the outbreak of the 1914 war is a persistent historical problem. The contradiction is obvious. Here was a movement that firmly proclaimed "proletarian internationalism", but which, when the time came to implement it, affirmed the necessity of "national defense". The concrete forms of this contradiction are illuminated by a study of the impact of the rise of imperialism on the internationalism of French and German socialists in the period leading up to the war, from the London Congress of 1896 to the resolution of the Agadir crisis in 1912. The Second International is a movement whose organizational and practical forms are rooted in a national framework, while its fundamental conceptions are those of internationalism. Imperialism reinforces this contradiction, and becomes at the same time the source of a concretization of socialist internationalism in theory, and of its abandonment in practice. Emphasizing the analysis of internationalism as a political rather than a cultural or sentimental phenomenon, this work demonstrates the existence of a chasm between the theoretical discourse and the practice of the movement. The rise of imperialism is accompanied by the rise of reformism within the socialist movement, which, along with other phenomena, reinforces its national tendencies. The national tendencies of the movement persisted at key moments, notably the imperialist crises of Tangier (1905) and Agadir (1911), to the point of calling into question the internationalist foundations of the movement.
Keywords: Modern history / Histoire moderne (UMI : 0582); crises; imperialism; impérialisme; international; internationale; internationalism; internationalisme; marxism; marxisme; reformism; réformisme; social-democracy; social-démocratie; socialism; socialisme

«La laïcisation des études médiévales» : l’Institut d’études médiévales de l’Université de Montréal et sa réforme académique de la Révolution tranquille, 1959-1968 - Robert, Martin (Université de Montréal, 2022)
This master's thesis analyses the institutional transformations of the Institut d'études médiévales of the Université de Montréal between 1942 and 1968. To do so, we focus on the effects of the Quiet Revolution on the Institut d'études médiévales, an institution of higher learning founded by the Dominican Order in 1930. Inspired by the Nouvelle Théologie outlined by Marie-Dominique Chenu, the Institute embraces a doctrinal raison d'être and uses scientific know-how to achieve it. By adapting the historical-critical method to infer the teaching of Thomism, the Institute represents an interesting religious-scientific amalgam to understand the effects of the secularization of the Université de Montreal on its structures, its culture, and its institutions. We describe the journey of this institution through La Grande Noirceur, the Quiet Revolution, and the secularization of the university’s Charter. Through the analysis of the archives of the Université de Montreal and the Canadian Province of the Dominican Order, we describe the institutional history of the Institut d'études médiévales according to the evolution of its hopes and of its functions at the university. Through the analysis of its mission statements, we describe how the Institute adapts to keep pace with the structural and cultural evolution within Quebec’s Quiet Revolution.
Keywords: Analyse du discours; Center for Medieval Studies; Centre d’études médiévales; Discourse analysis; Faculty of Arts and Sciences; Histoire des universités; Histoire institutionnelle; History - Canadian / Histoire - Canadienne (UMI : 0334); History of universities; Institut d’études médiévales; Institute of Medieval Studies; Institutional history; Laïcisation; Nouvelle théologie; Philosophie; Philosophy; Quiet revolution; Révolution tranquille; Secularization; University of Montreal; Université de Montréal

L’envergure du poète dans la pensée de George Sand - Ramsay-Piérard, Anne (Université de Montréal, 2022)
George Sand, born Aurore Dupin (1804-1876), was one of the most prolific writers of the July Monarchy (1830-1848). Her monumental work focuses on a myriad of subjects, which are often studied from the perspective of the ideal. Among other things, Sand was interested in the notion of the poet-artist, which refers to an ideal artist. This notion, specific to this period, is distinguished from the other poet, which is a writer. While the meaning of the notion of poet-writer is well determined, that of poet-artist is subject to a vague and subjective definition. For her part, Sand considers that the poet-artist designates both an artist and a philosopher. This proposition, which is clearly stated, constitutes a central axis to all the artistic thought that she develops. This is what is explored in the present work, through three themes of George Sand's artistic thought. Each chapter is devoted to one of these themes, with an attempt to organize the artistic thought of Sand. The theme of the brotherhood of the arts will be studied first. This typically romantic theme, omnipresent in Sand's writings, perceives the different disciplines as forming a whole. Then, the hierarchy of arts will be reviewed: George Sand considers that music is the superior discipline, compared to some of her contemporaries who believe that poetry is the superior discipline. Finally, George Sand perceives a figure of genius in her writings, which comes close to the ideal artist. All these themes are studied in close relation to the usual visions found under the July Monarchy.
Keywords: Artiste idéal; Brotherhood of arts; Fraternité des arts; Genius; George Sand; Génie; Hierarchy of arts; History - European / Histoire - Européenne (UMI : 0335); Hiérarchie des arts; Ideal artist; July Monarchy; Monarchie de Juillet; Poet; Poète; Romanticism; Romantisme

La vie intime en Grèce ancienne : entre pureté et impureté - Nicholls, Dorothée (Université de Montréal, 2022)
This master’s thesis concern impurity in Greek religion and more specifically the miasma related to the intimate life. The aim of this study is to provide a comprehensive portrait of intimate life through the analysis of religious inscriptions and literary documents. The examination of these sources allow the identification of the modalities for entering the temple and the processes necessary to regain its state of purity. This first objective leads to a second: I aim to formulate an explanatory theory on the origin of impurity in ancient Greece that departs from the traditional and interpretative theories by taking into account the contribution of cognitive science and social psychology to this question. Divided into four chapters, the research first focuses on the impurity of menstruation, a deeply intimate event and little studied due to persistent modern taboos. The second chapter dwells on the impurity of sexual relations. More specifically, this second section analyzes the differences between the miasma caused by relationships between spouses and by extramarital relationships. The third chapter deals with events related to motherhood, namely childbirth, abortion, miscarriage and breastfeeding. The juxtaposition of several types of impurity allow the identification of certain trends or similarities. Finally, the fourth chapter consists of the exploration of the biological and cognitive theories that could explain the origin of impurity in Ancient Greece. This final chapter seek to conclude that impurity is partly due to cognitive processes and reflexes which have been socially reinforced by the Greek religion.
Keywords: Ancient history / Histoire de l’Antiquité (UMI : 0579); Greek religion; Religion grecque; abortion; accouchement; allaitement; avortement; breastfeeding; childbirth; epigraphy; fausse-couche; impureté; impurity; intimate life; menstruations; miscarriage; relations sexuelles; sexual relationship; vie intime; épigraphie

«Jeunes filles, voilà vos mères. Soyez dignes d’elles!» : modèles moraux et patriotiques de la femme française dans les biographies collectives féminines (1886-1893) - Le Rouzès-Ménard, Eveline (Université de Montréal, 2022)
As Jules Ferry’s Laws (1881-1882) rendered French primary education secular, mandatory and free, most republican pedagogues designed educational lessons developed on the principle of emulation. By promoting national historical figures and heroes, they mostly sought to provide moral and patriotic models, embodying republican values, to all young boys and girls. Many examples offered in classrooms illustrated and perpetuated a vision of French society based on the sexual division of labor: masculine icons expressed public, military, and political roles while feminine icons revealed private, domestic, and maternal attributes or responsibilities. Previous academic studies on the subject explored almost exclusively the content of primary official textbooks. Meanwhile, feminine models presented in children’s literature, especially within popular collective biographies, have not yet been the object of extensive historical research. Although this literary genre was consumed in great numbers by the public in fin-de-siècle France, it has until recently always been sidelined in academic studies. However, it can be argued that collective biographies showed a significant diversity of role models to French youth. Thereby, this Master’s thesis proposes an analysis of moral, civic, and patriotic icons, which schoolgirls were meant to emulate, included in three collective feminine biographies published during the years following Ferry’s school system reforms (between 1886 and 1893). This study attempts to define the « feminine » and « French » identity shaped by the authors of these books, which recommended less conventional and alternative models, different from traditional examples usually seen in official textbooks of the period.
Keywords: Biographie collective féminine; Enseignement primaire; Female role models; Feminine collective biography; Feminine identity; France; Gender studies; Genre; Grandes femmes françaises; Great French women; Histoire nationale; History - European / Histoire - Européenne (UMI : 0335); Identité féminine; Instruction civique et morale; Modèles féminins; Moral and civic education; National history; Patriotism; Patriotisme; Primary education; Third Republic; Troisième République

Économie de la réputation commerciale. Une histoire du crédit marchand à Montréal au 19e siècle - Lapalme, Alexandre (Université de Montréal, 2022)
This thesis examines the credit records between 1847 and 1872 of the Montreal branch of the Mercantile Agency, among the most important credit bureaus in 19th century North America. The 19th century saw the acceleration of transatlantic trade. Montreal, located between Great Britain and the United States, was at the crossroads of the economic expansion. In this period, commonly referred to as the transition to capitalism, the legal, commercial and financial institutions of the metropolis were forced to adjust. In the financial sector, the state was compelled to adopt bankruptcy laws to lessen the negative effects of bad debts and to encourage and support the spread of commercial credit. However, because of limited accessibility, and the complexity and costs of the procedure, the laws were unable to fully guarantee the recovery of loans and were deemed unsatisfactory by the business community. The thesis claims that the emergence of credit agencies responded to the needs of the business community to address problems of information asymmetry. These agencies, like the Mercantile Agency, established a type of self-regulation of commercial credit. They provided information on risk to lenders. To a large extent, the information gathered represented the opinion of the Montreal merchant community. The credit offices of the Mercantile Agency used this information to generate rankings of the credit worthiness of merchants. The information was disseminated to the Agency’s network of subscribers. In this fashion, the Agency contributed to the construction of an economy of reputations. The research, which is inspired by contributions to the new history of capitalism, explores the effects of the construction of the economy of reputations on the relationship between lenders and borrowers. I find that the structure of the relationship favored creditor over debtors. The chapters of the thesis describe the role of reputation in the creditor-debtor relationship, the determinants adopted to measure credit worthiness, and the tensions and conflicts that emerged in the economy of reputations.
Keywords: 19e siècle; 19th century; =CL; Bankruptcy laws; Bureaux de crédit; Canadian history / Histoire du Canada (UMI : 0334); Capitalism; Capitalisme; Commerce; Commercial credit; Credit bureaus; Crédit marchand; Histoire; History; Lois sur les faillites; Montreal; Montréal; Reputation; Réputation

La transformation poétique de Judith dans le poème en vieil-anglais "Judith" : de veuve pieuse juive à vierge héroïque anglo-saxonne - Lauzon, Nicolas (Université de Montréal, 2022)
Between the second half of the10th century and the beginning of the 11th century, the Old English poem Judith was written in one of the great monastic centers of the Anglo-Saxon world. This poem, based on the biblical text of the Book of Judith, is the result of the meeting of traditional biblical material and the heroic Anglo-Saxon poetic tradition. From this encounter emerges a work celebrating biblical history and the moral teachings it carries, as well as the values of Anglo-Saxon aristocratic culture and heroism. The poem Judith is therefore a strong example of cultural adaptation of biblical material. This thesis is concerned with this question of cultural adaptation, but even more with that of the coexistence of different traditions and cultural references within the Old English poem Judith. Throughout this thesis, it will be a question of determining the nature of this coexistence, namely how is it articulated? Does the poem present a case of hierarchization between these different cultural references? Or would it be fairer to speak of cultural pluralism and parallelism? Finally, how important is the historical context of the 10th and 11th centuries in the development of this poem? Following our analysis of the poem and its historical context we will demonstrate that Judith is a work of cultural parallelism where each cultural reference is presented without the need for hierarchy. In addition, we will demonstrate that the Judith is the result of changes in Anglo-Saxon society between the 9th and 11th centuries and the political and military instability caused by conflicts between Anglo-Saxons and Scandinavians.
Keywords: Anglo-Saxons; Anglo-saxon history; Anglo-saxon poetry; Heroic; Heroic poetry; Histoire anglo-saxonne; History - Medieval / Histoire - Médiévale (UMI : 0581); L'héroïque; Littérature médiévale; Medieval litterature; Old english poetry; Poésie anglo-saxonne; Poésie en vieil-anglais; Poésie héroïque; Syncretism; Syncrétisme; Viking

La critique de la chrétienté chez la revue catholique de gauche Maintenant (1962-1974) - Lafontaine, Anthony Maxime (Université de Montréal, 2022)
Maintenant is a French Canadian catholic paper created by the Dominican Order and published from 1962 to 1974. Its authors are proponents of Emmanuel Mounier’s personalism. According to this philosophy, the true catholic faith calls for believers to positively transform profane society following evangelical lines. Maintenant’s writers postulate that Québec’s numerous catholic institutions are an obstacle to this ideal : rather than encourage believers to reshape their environment, these institutions seek to isolate them from society in order to shield them from nefarious beliefs and temptations. This « system », la chrétienté, is relentlessly criticized and painted as the main cause behind the observed religious decline. Indeed, the monthly publication argues that these institutions are indissociable from an authoritarian stance that breeds conformism and religious ignorance. From 1965 onward, secularism in Québec dramatically reduces the Catholic Church’s institutional presence. The Liberals’ « Bill 60 », for example, makes the government the primary actor in matters of public education. In turn, the intellectuals of Maintenant gradually shift their focus from la chrétienté to secularism’s impact on religious belief and practice. Convinced that Catholicism and the rising secular mentality can coexist, they put forward ideas of pastoral, liturgical and ecclesiological reform aimed at reconciling the two. These propositions are deeply influenced by the Second Vatican Council (1962-1965) during which a majority of the clergy is won over by personalist ideals. The paper’s authors are nonetheless disappointed by the reforms emanating from the works of the Council as they are deemed unambitious and badly implemented.
Keywords: Catholic Church; History - Church / Histoire - Église (UMI : 0330); Laïcité; Maintenant; Personalism; Personnalisme; Quiet Revolution; Révolution tranquille; Secularism; Église catholique

Peuple de l'ombre, peuple universel : les résistants et les anciens résistants français face à l'Empire et la décolonisation (1940-1962) - Houle, Vincent (Université de Montréal, 2022)
This thesis examines French resistants and ex-resistants’ ties with the Empire, during and after the Second World War. It therefore explores a broader timeframe and geographic area than what previous historiography about French Resistance has offered up until now. In analyzing French Resistance newspapers and constitutional projects from 1940 through 1944, the thesis reveals that while the principles of the Third Republic were repudiated by French society at the time, one particular element remained: the idea of the civilizing mission. Then, through the study of numerous personal testimonies covering the years between the Liberation and the end of the Algerian War, the research offers a profound and nuanced insight on ex-resistants views of the Empire and their point of view on their country's colonial system. After 1944, the power dynamic shifted to the resistants: they were no longer dominated by a violent German state, they were now the ones enforcing domination to the colonies. The testimonies reveal the internal conflict French ex-resistants were dealing with when faced with the problems of decolonization. It also shows how the principles, for which they risked their lives during the war, were modified or reshaped to fit with their views on how to deal with the colonies’ wishes for emancipation. In examining how the war against fascism and the Vichy regime impacted personal attitudes towards the Empire and the exercise of domination, the study offers a new perspective on the French Resistance and French Imperial history from 1940 to 1962, one that accounts for political and economic imperatives as well as for the importance of the different interpretations of the Republic's core principles for these individuals. The individuals were selected because of the importance of their political, social or military commitments through the period. By focusing on the relationships between these successive commitments, the analysis enlarges the scope through which the French Resistance must be understood.
Keywords: Algeria; Algérie; Decolonization; Deuxième Guerre mondiale; Décolonisation; Empire français; European history / Histoire de l’Europe (UMI : 0335); France; French Empire; French Resistance; Imperialism; Impérialisme; Indochina; Indochine; Republicanism; Républicanisme; Résistance française; Second World War; Universalism; Universalisme

An Investigation of Iron Age to Classical Animal Bone Deposits in Northern Greece (Macedonia) : Argilos, Karabournaki and Kastri Thassos - Gkotsinas, Angelos (Université de Montréal, 2022)
Over the past decades, the zooarchaeological research in the Macedonian region of Northern Greece, has mostly focused on materials from Neolithic and Bronze Age sites. Thus, the available data render our understanding of animal husbandry in the Early Iron Age, Archaic and Classical periods in this area rather fragmentary. This doctoral research aims to address these gaps, investigating – for the first time as a whole – the issue of animal husbandry, a crucial domain of the primary economy, in the region of Macedonia from the Early Iron Age to the Classical era. The study is based on primary datasets of animal bones remains recovered from three well- excavated settlements, two in the mainland (Argilos, Karabournaki) and one in the island of Thassos (Kastri). The analysed data provide an opportunity to explore the animal exploitation in these three settlements, investigating animal management; cooking techniques; consumption and discard strategies, having first disentangled all potential depositional pathways to the formation of the sample assemblage. Additionally, the data are compared to the available published data from the Macedonian region in order to enlighten the peculiarities of each assemblage in relation to the management of domestic and wild fauna. Moreover, relevant paleoenvironmental and isotopic analyses have triggered a vivid discussion regarding the extent to which the environment affected the animal herding and feeding strategies in this area. The management strategies of the main domestics in the area under study, suggest a rather heterogenous profile between the settlements, most probably due to the economic priorities, the regional environmental conditions, and the geomorphological restrictions. The nutritional and the raw material needs were complemented by the exploitation of the wild fauna, including a variety of both terrestrial and marine species. Similar carcass and discarding practices were observed within all settlements, revealing aspects of intra-communal organization. Moreover, during the Archaic and Classical era, common practices in animal burials suggest the existence of somehow common perceptions among the local societies, however, in terms of ritual sacrifices, seemed to be a distinct differentiation between the population groups. The results are discussed in the frame of the Aegean basin, contributing to the ongoing discussion regarding animal management, the mobility of livestock husbandry, the degree of integration between herding and arable farming, the Olympic sacrifice, and the exploitation of natural resources during the first seven centuries of the first millennium BC.
Keywords: Animal husbandry; Animal management; Archaeology / Archéologie (UMI : 0324); Argilos; Gestion des animaux; Greece; Grèce; Isotopes; Karabournaki; Kastri Thassos; Macedonia; Macédoine; Pastoral economy; Transhumance; Zooarchaeology; Zooarchéologie; Économie pastorale; Élevage

Le culte de Liber Pater en Italie : identité divine et pratiques rituelles - Guénette, Maxime (Université de Montréal, 2022)
This dissertation is structured in three distinct sections: in the first one, we examine the divine figure of Liber Pater and the perception of this divinity in Roman Italy. Liber never ceases to surprise scholars, mostly because of his association with Dionysus, so it is necessary to address a simple but crucial question: who is Liber Pater? We emphasize in this section that Liber is an agrarian deity recognized within the pantheon of Rome and thus receives a public cult through the Liberalia and the triad that he forms with Ceres and Libera. The tutelage of Liber on libertas is also questioned: rather than understanding it in terms of political freedom, we must rather focus on a physical and mental freedom. In the second section, we establish a connection on the Italian territory between Liber and Dionysus-Bacchus thanks to the process of acculturation that took place with the arrival of Dionysus in Magna Graecia in the 8th and 7th century BC. We then explore, through the tutelage of Liber and Bacchus over wine as well as the repression of the Bacchanalia, the heterogeneous forms that the rituals and cults dedicated to these deities may have taken. Finally, our last section dives into the cult of Liber in Italy in the Early Empire. To do so, we use the methodological framework of lived ancient religion, which focuses on the spectrum of religious strategies that can be put in place to communicate with Liber, be it through donation, prayer, gesture, sacrifice, etc. This model of analysis gives us the opportunity to focus on the lived worship of Liber, therefore bringing us closer to the religious experience of individuals. We demonstrate, through an epigraphic corpus comprising several types of inscriptions, that numerous communication strategies were used, notably the rituals of votum, dedicatio, and consecratio through the donation of objects such as altars and statues. In groups, these strategies become more complex since the associative phenomenon produces a significant cult diversification: several Roman associations, all different from one other in their practices and composition, honored Liber and his benefits.
Keywords: Ancient history / Histoire de l’Antiquité (UMI : 0579); Bacchus; Dionysos; Dionysus; Empire romain; Epigraphy; Italie romaine; Liber Pater; Lived Ancient Religion; Religion romaine; Roman Empire; Roman Italy; Roman religion; Épigraphie

Les représentations des Premiers Peuples et le colonialisme d’occupation dans les manuels scolaires d’histoire (1920-1960) - Gaudreault, Benoit (Université de Montréal, 2022)
My master’s thesis examines the representations of First Peoples in French-language history textbooks produced and used in Quebec between 1920 and 1960, with a particular focus on those intended for elementary school children. This research is at the crossroads of studies on Quebec colonialism, childhood history and the study of representations. Several theories emanating from visual studies, othering and performance studies are also mobilized in my study of history textbooks. By positioning itself at the intersection of this mosaic of historiographies and conceptual approaches, my master’s thesis answers the following questions: how are the First Peoples in Canada represented in French-language history textbooks produced between the 1920s and the 1960s and to what extent are these representations at odds with the previous period? How are these representations mobilized in the Quebec colonial imagination? How is the colonial image of the ‘imaginary Indian’ received, appropriated and performed by children? My study contributes to a historiography exploring history of representations of the First Peoples in history textbooks since the beginning of public education in Quebec. The first chapter explores three historiographical fields on which my dissertation draws: children's history, settler colonialism, and representations of First Peoples in North American popular culture. Chapters two and three are devoted, in order, to the analysis of history textbooks produced between 1920 and 1950 and those between 1950 and 1960. I show that the figure of the Indian is mobilized by the authors of the first period’s textbooks to justify the dispossession and colonial violence of the past, notably through the use of political, moral and genealogical arguments. In the latter period’s, more nationalistic series of textbooks, the authors reiterate these same ideas, but with a stronger emphasis on the idea of the ‘civilizing mission’ to the point of cleansing the Quebec historical narrative of its original violence. Furthermore, I argue that these textbooks show the continuation of colonialism in the present. First Peoples no longer disappear from the narrative after the Conquest, as was the case in history textbooks before 1950, but they are still subject to a colonial discourse that denigrates and invisibilizes them, while attempting to justify the dispossession of their lands.
Keywords: Altérité; Autochtones; Canadian history / Histoire du Canada (UMI : 0334); Childhood; Colonialisme d'occupation; First Peoples; History; Manuel scolaire; Otherness; Premiers Peuples; Représentations; Settler colonialism; Textbook; Visual studies; Éducation

La presse féminine italienne de l’entre-deux-guerres : une question d’opinion (1922 – 1937) - Gagné-Lebel, Andréanne (Université de Montréal, 2022)
This master’s thesis analyses Italian women discourses on their living conditions in the feminine press during the fascist era, from 1922 to 1937. On the basis of three publications, l’Almanacco della donna italiana, La Donna Italiana: rivista mensile di lettere, scienze, arti e movimento sociale femminile and Il Giornale della donna, which will become, in 1935, La Donna Fascista, this study tries to demonstrate that maternity, employment and leisure are all present in the discourses, and that they have been written about openly. It is possible to note an evolution of the feminine points of view with the different events happening at the time, like Matteotti’s assassination and the new work legislation. Journalists share their ideas with multiple techniques. They use the parameters of the fascist regime to justify the role and services to which they pretend, as well as the gendered society division to self-assign some tasks and the ideals carried by the ideology to justify points of view. Therefore, despite freedom of expression restrictions during Benito Mussolini’s regime, women do have some latitude in the discourses related to their living condition, which have the particularity of being written strictly for a female audience. This thesis demonstrates the particularities of women’s discourses in a totalitarian society. To do so, the publication selection has been studied by statistical analysis first to seek out common subjects and journalists, and then by comparative analysis to demonstrate similarities and differences in the topics’ treatment.
Keywords: Emploi; Employment; Entre-deux-guerres; European history / Histoire de l’Europe (UMI : 0335); Fascism; Fascisme; Feminism; Femmes; Féminisme; Gender; Genre; Hobbies; Interwar; Italie; Italy; Journalism; Journalisme; Loisirs; Maternity; Maternité; Women

«L’autisme, cet inconnu» : représentations expertes et populaires du trouble du spectre de l’autisme dans les quotidiens montréalais de 1970 à 1998 - El-Sabbagh, Marianne (Université de Montréal, 2022)
In 1988, British gastroenterologist Andrew Wakefield describes a new type of phenomenon. According to his Since 1970, specialists have noticed an upsurged in the amount of diagnosis of autism spectrum disorder (ASD) in Quebecois children and children across the world. Once considered “unfortunate souls” suffering from an “unknown illness”, autism is now a disorder the public is now well-aware of, and on which multiple studies were conducted. However, with the publication of a study in 1998 claiming the origins of the disorder is the measles, mumps, and rubella vaccine (MMR vaccine), the conversation on autism is now polluted by the question of its origins, to the point few people have considered the portrayals of autism and autism in the period leading up to this publication, when the years 1970 to 1990 represent an important period in terms of the evolution of autism’s markers and its treatments, in Quebec in particular. To this end, a series of articles from daily newspapers La Presse and Le Devoir concerning autism over the period 1970-1998 were analyzed in order to highlight three important axes in the present research: the characteristics of autism, the causes of the disorder as well as the care of autistic people, and in particular, young autistic people. From this analysis, we first retain a transformation in the perception of the autistic, where the ‘idiot’ child of the 1970s becomes a misunderstood genius in the 1990s. Simultaneously, we note the appropriation by popular discourses of the role of parents (and mothers especially) on the origins of autism, as well as the popularization of the myth of giftedness in the 1990s. In order to answer these questions, the present dissertation hopes to question the thickness, complexity and temporality of these representations, and do so by trying to observe if those representations interact or are independent from each other during this period, and if we see through the press tensions between discourses used by both communities, or a mixture of mutual appropriations.
Keywords: History - Canadian / Histoire - Canadienne (UMI : 0334); autism; autisme; caractéristiques; care; causes; characteristics; intégration; media; médias; prise en charge; representations; représentations

Honneur et individualité : dynamiques identitaires dans les sagas des Islandais - Denis-Blais, Maxence (Université de Montréal, 2022)
This study aspires to place thirteenth-century Iceland more fully within the historiographical debate on the individual in the Middle Ages, which has tended to focus on continental Western Europe. It interrogates the perception that the ancient Icelanders had of themselves in relation to the notion of individualism. In turn, it seeks to identify the sustained relationship with the collective, to determine if the Icelanders could conceive and define themselves beyond group structures or membership. Analysis of the content of the sagas of Icelanders (Íslendingasögur), a literary genre specific to Iceland, makes it possible to formulate a history of mentalité for this purpose. The notion of honor, a central theme in the texts, serves to evaluate the degree of individuality accorded the ancient Icelanders. The various dimensions of honor as expressed in the sagas are then dessected to answer this question. Honor is first considered in its relation to reputation. The importance of the idea of reputation as well as the process by which it is established is then observed. Analysis of how honor and its pursuit are motivating themes in the sagas are then considered. Finally, honor is perceived under the theme of the perception of oneʼs dignity and its social implications.
Keywords: Collectif; Collective; Dignity; Dignité; History - Medieval / Histoire - Médiévale (UMI : 0581); Honneur; Honor; Iceland; Identity; Identité; Individu; Individual; Islande; Middle Ages; Moyen Âge; Reputation; Réputation; Saga; Scandinave; Scandinavian

«Je vais retourner chargé de reliques» : la dévotion aux martyrs des catacombes romaines au Canada (1830-1930) - Dahan, Michel (Université de Montréal, 2022)
On 22 June 1845, a curious religious procession took place in the streets of Montreal. A “huge crowd” gathered to accompany through the city the body of a man exhumed from the Roman catacombs. His bones had been shipped to Montreal and placed in a wax figure representing a Roman soldier. Presumed to have died for his faith, this martyr was carried through the streets at arm’s length amid incense and hymns. Surprisingly, this procession was not an isolated one. From 1830 to 1930, the remains of dozens of presumed Christian martyrs extracted from the Roman catacombs were sent to Canada. In Halifax, Rimouski, Joliette, Toronto, and Windsor, they attracted the faithful and the curious. Adopted as powerful intercessors, these foreign saints would shape the beliefs, representations, and identity of generations of Catholics. Around their relics, a whole devotional universe would develop and maintain various and complex relations with society. These relics provide us with a unique window into nineteenth-century Canadian society. This thesis makes a significant contribution to historiography by exploring for the first time the topic of ultramontane devotions in Canada. It studies the deployment of the cult of Roman martyrs and their relics in the Canadian Church and reconstitutes the development of this devotion from a cultural history perspective. Using archival documents found on both sides of the Atlantic, this thesis examines how Canadians discovered, sought, and adopted this foreign devotion. In reality, this infatuation for Roman relics is primarily a transnational phenomenon that is part of the profound changes that the Catholic Church experienced in the nineteenth century, driven in particular by the Ultramontane movement. Therefore, it seeks to situate the presence of relics from the catacombs in Canada in its global context while considering its Canadian particularities. It rests on a considerable number of novel sources drawn from more than thirty archival centers. With the help of these documents, it examines the different facets that this devotion had, whether in cities or the countryside, among English-speaking or French-speaking communities or in predominantly Catholic or Protestant environments. The first chapter reveals the fascination with Christian Rome among nineteenth-century Canadians and the importance that the catacombs and their martyrs had in the minds of the Catholic faithful. The second chapter identifies the many networks uniting the Canadian Church with Rome, and more broadly with Europe, that allowed the acquisition and shipping of relics to Canada. It replaces this devotion in a larger framework by linking it to other manifestations of this expression of piety elsewhere in the world. It pays particular attention to the exchange of goods between the Italian peninsula and North America by studying the commercial routes that allowed the circulation of relics. The remaining three chapters are devoted to the presentation, the reception, and the adoption of catacomb saints in Canada. They examine the art of molding wax bodies containing relics and the symbolism of these recumbent-reliquaries, before describing the religious ceremony organized to mark the arrival of a new martyr. Finally, this thesis explores the faithful’s various expressions of piety: patronages, prayers, indulgences, and claims of miracles. It examines the attachment but also the opposition and the tensions provoked by Roman relics within society. This research demonstrates the influence that foreign religious devotions held in the spiritual lives of Canadians and the many connections uniting Canadian society with Europe. It also testifies to significant changes in the devotional universe of the nineteenth century. But above all, it highlights the profound transformations of both culture and mentalities and particularly of beliefs, emotions, and the idea of death. This study contributes to a better understanding of the religious past of several generations of Canadians by studying a devotion that has now completely been forgotten.
Keywords: Canadian catholicism; Canadian history / Histoire du Canada (UMI : 0334); catholicisme canadien; corpi santi; corps saints; dévotion religieuse; gisants en cire; relics; religious devotion; reliquaires; reliquaries; reliques; ultramontanism; ultramontanisme; wax bodies

Langues, culture et représentation du pouvoir : Jean duc de Bedford, régent du royaume de France (1422-1435) - Cormier, David (Université de Montréal, 2022)
From 1422 the Englishman John of Lancaster (1389-1435), duke of Bedford, was regent of his young nephew’s French kingdom. Because the treaty of Troyes (1420) provided for a long-lasting English presence in France, the regent had to put in place a social domination structure based on consent rather than coercion. In this context, the duke of Bedford devised a cultural and language policy inspired by the attitudes of the most prominent members of the Valois family. It allowed him to bolster support for his regime and legitimize his power. This policy is the main object of our research. We first propose to examine each element of Bedford’s cultural policy. His magnificent households, precious manuscripts and generous patronage were outward symbols of the might and stability of English rule in France. These possessions also allowed their owner to present himself as a legitimate member of continental courtly society. As such, they were a mean to strengthen the bond with his most important ally, his brother-in-law Philip, duke of Burgundy. At the same time the regent depicted himself, and by extension Henry VI, as the legitimate ruler of France by actively imitating past French kings. Some of his cultural enterprises can be conceived as propaganda. However under careful scrutiny these representations of power appear to have been intended not only for the conquered, but also for the conquerors themselves. We devote a second chapter to the exercise of power through writing. We analyze the duke’s production of written documents, both sides of the Channel, in light of its compliance to or defiance of French diplomatic tradition. In itself, the adoption of local practices and language was both respectful of the spirit of the treaty of Troyes and a convenient way to conceal the dynastic rift between Valois and Lancaster. On the other hand, the continued use of typical English documents in Bedford’s organization of the military reveals the limited extent of his acculturation. We also consider the important role of the French secretaries in the coordination between the two kingdoms, which in theory were supposed to be kept separate. Some of them were so involved in English affairs that they moved to England to serve Henry VI. In the end however the English bureaucracy remained mostly unaffected by extraneous innovations. Nonetheless, the very significant linguistic shift it underwent was contemporary, and linked, to the demise of Lancastrian France. The last chapter examines the contribution of other important figures of the anglo-burgundian cultural environment. The continental activity of magnates like Richard Beauchamp and soldiers like John Talbot exemplifies the relative vitality of courtly life in Lancastrian France and highlights the adoption of some elements of French culture by the English there. The subsequent patronage, circulation of texts and artists and, ultimately, the internalization of the Lancastrian French narrative, led to the transformation of English culture. This cultural appropriation contributed to the perpetuation of French language and literature in fifteenth-century England. Paradoxically, it also reinforced a properly English identity.
Keywords: Culture; Fifteenth century; France lancastrienne; French language; Guerre de Cent Ans; Henri VI; Henry VI; History - Medieval / Histoire - Médiévale (UMI : 0581); Hundred Years' War; Jean de Lancastre; John of Lancaster; Lancastrian France; Langue française; Propaganda; Propagande; XVe siècle

Les cultes des eaux douces à Rome d’après les sources de la République tardive et du Haut-Empire : une idiosyncrasie culturelle? - Buruiana, Traïan (Université de Montréal, 2022)
This doctoral thesis in history focuses on the religious relationship between the ancient Romans and the freshwater which they lived nearby as inhabitants of a river town. This study starts from the observation that Romans are known for their technical knowledge of water and their aqueducts. However, religious beliefs associated with water have yet to be fully examined and remain scattered throughout historiography. To fill this gap, this study presents a synthesis of the aquatic cultures of the Romans from literary, archaeological, and epigraphic sources, dating mostly from the Late Republic and the High Empire (1st century BC. 3rd century)
Keywords: Dieux; Eau; Festivals; Fontaines; Fountains; History - General / Histoire générale (UMI : 0578); Juturne; Mythes; Myths; Neptune; Nymphs; Religion; Rites; Rituals; Rome; Source; Temples; Tibre; Water

La presse nationale française et la remise en question du traité de Versailles par l’Allemagne (1933-1939) - Boulanger, Xavier (Université de Montréal, 2022)
During the 1930s, France was hit by a political, economic, and diplomatic crisis which revealed many divisions in society. French journalists, seeking a solution to the national crisis, showed a particular interest towards their neighbor across the Rhine after the nomination of Hitler as Chancellor of Germany on January 30th, 1933. Hitler took advantage of France’s weakness and divisions to question but also oppose and act against the clauses of the Treaty of Versailles until the outbreak of World War II on September 1st, 1939. The objective of this research is to analyze how the French national press reacted to German revisionism from 1933 to 1939. In this context, the press’ perception of Hitler’s actions and how its opinions changed (or not) over time reveals the ways in which French newspapers interpreted events in Germany that affected France itself. By consulting editorials and opinion articles from five daily newspapers of different political orientations, namely L’Action française, L’Humanité, Le Figaro, Le Petit Parisien and Le Temps, this memoire analyse the opinion of the French national press on the revision of the Treaty of Versailles. This study contributes to the historiography of the interwar period and France’s reaction to German aggression in two ways. First, it shows that the press was not blind to Hitler’s revisionist plan. It also demonstrates that the French press remained divided concerning the actions of Nazi Germany until 1939. The protection of the Treaty of Versailles’ clauses and its system, which maintained the balance of power in Europe, polarised the French press and created a weakened national feeling until the outbreak of World War II. German revisionism fuelled the disagreements in the daily newspapers studied from 1933 to 1939.
Keywords: 1933-1939; French national press; German revisionism; History - European / Histoire - Européenne (UMI : 0335); Le Figaro; Le Petit Parisien; Le Temps; L’Action française; L’Humanité; Treaty of Versailles; franco-german diplomacy; presse nationale française; rapports franco-allemands; révisionnisme allemand; traité de Versailles

Les transformations du culte impérial romain au IVe siècle : entre continuité et adaptation - Beauchemin-Brisson, Étienne (Université de Montréal, 2022)
The study of the Roman imperial cult in the 4th century has often been relegated to the background in research relating to this subject. The imperial cult has even often been relegated to the same fate than the rest of the Roman traditional cults. However, in the light of period sources and the work of certain historians, such as Louis Bréhier, the imperial cult seems to have survived this prognosis of disappearance. More interesting still, the imperial cult appears to have transformed and adapted to the new reality offered by a Christianizing Roman Empire while the power of the emperor was becoming more sacred. The work presented in this thesis parallels the metamorphosis experienced by the imperial cult with the strengthening of imperial power during the fourth century, while comparing the evolution of the perception that Christians had of this fundamentally traditional institution. As mentioned above, the study is based on a body of contemporary sources, ranging from Christian homilies to epigraphic sources which will corroborate the information found in the work of several historians who have studied the topic. Overall, this research demonstrates that the imperial cult succeeded in shedding religious connotations that Christians considered problematic while continuing to function and occupy a central place in the life of the Romans. This, together with an imperial power expressed in absolute terms, initiated the metamorphosis of the imperial cult into a "monarchical cult", exalting even more the emperor's power for centuries to come.
Keywords: 4th century; Ancient history / Histoire de l’Antiquité (UMI : 0579); Ancient religion; Antiquité tardive; Christianisme antique; Culte impérial; Early Christianity; Empire romain; IVe siècle; Imperial cult; Imperial power; Late antiquity; Pouvoir impérial; Religion antique; Roman Empire

Les failles d'un droit nouveau : La défense des criminels de guerre nazis en 1945 - Revue Histoire, Idées, Sociétés - UQAM - Racine, Rosalie (Revue Histoire, Idées, Sociétés, 2022)
En 1945, quelques mois après la fin de la Seconde Guerre mondiale, débutent les premiers procès contre les criminels de guerre nazis. Ces derniers, dont l’organisation a rapidement été ajoutée aux objectifs de guerre des Alliés, doivent permettre aux nations victimes des crimes nazis de juger et de châtier les criminels de guerre. Cet article cherche à démontrer la manière dont les avocats de la défense ont pu exploiter les failles dans le droit mis en place par les Alliés et les réponses de la poursuite. Le présent article met donc l’accent sur les différents arguments amenés par les avocats de la défense qui, par leurs actions et leur volonté de respecter l’intégrité des procédures judiciaires, ont également contribué à démontrer la bonne volonté des Alliés à instaurer un nouveau système qui soit juste et non basé sur la vengeance.
Keywords: =CL

Introduction - Sollai, Luca (Les cahiers d’histoire, 2022)
Keywords: =CL

De mémoire et d’histoire - Sollai, Luca; Saul, Samir (Cahiers d'histoire, 2022)
Number: 2 Volume 38, numéro 2, automne 2022 De mémoire et d’histoire Sous la direction de Luca Sollai et Samir Saul
Keywords: =CL

11Q23, Introduction, traduction et notes - Bellavance, Éric (La bibliothèque de qumrân, 2022)

4Q183, Introduction, traduction et notes - Bellavance, Éric (La bibliothèque de qumrân, 2022)

4Q178, Introduction, traduction et notes - Bellavance, Éric (La bibliothèque de qumrân, 2022)

4Q171, Introduction, traduction et notes - Bellavance, Éric (La bibliothèque de qumrân, 2022)

4Q173, Introduction, traduction et notes - Bellavance, Éric (La bibliothèque de qumrân, 2022)

Isotopic evidence for animal management strategies at Archaic and Classical period Argilos, Greece - Alagich, Rudolph; Gkotsinas, Angelos; Perreault, Jacques Y.; Bonias, Zisis; Smith, Colin (Journal of Archaeological Science: Reports, 2022)
This paper utilizes the stable carbon and nitrogen isotopic composition of bulk animal bone collagen to better understand animal management practices in Archaic and Classical period Argilos in northern Greece. The results from Argilos are compared with data from other sites in northern Greece to provide new insights into herd management in the region over time. Our results reveal some changes in cattle and pig diets at Argilos between the Archaic and Classical periods. Throughout both periods cattle and caprines exhibit evidence of having consumed C4 vegetation, likely obtained from the nearby salt marshes in the Strymon river delta. This dietary regime is similar to that observed at other north Aegean sites dating back to the Neolithic, suggesting that the long tradition of animal herding in the marshes was an environmentally specific practice in the region.
Keywords: Agriculture; Argilos; Classical period; Greece; Stable isotopes

Forme d’entreprise et responsabilité personnelle dans la liquidation des dettes de la Compagnie de la Nouvelle-France - Dewar, Helen (Revue d'histoire de l'Amérique française, 2022)
The historiography on the Compagnie de la Nouvelle-France (CNF) focuses primarily on its role in the colonization of New France. By examining its form, I resituate the CNF in the larger history of European experimentations with the joint-stock company. The liquidation of the company’s debts in the 1630s and 1640s forced associates, directors, and jurists to articulate their understanding of who was liable for the enterprise’s financial health. Evaluating the legal and moral arguments of the parties concerned, I argue that the complexity of the liability of associates and directors resulted from the intersection of corporate, monarchical and commercial worlds.
Number: 4

“No Women of the World Hate War and Seek Peace More than the Colored Women”: Mary Church Terrell’s Bid for Racial Justice and Women’s Rights in 1919: making peace in a disordered world - Siegel, Mona; Ingram, Norman; Bouchard, Carl (Beyond the Great War: Making Peace in a Disordered World, 2022)
"Was the end of the First World War a catalyst for progress or the harbinger of future conflict? The essays in this collection address the impact of the end of the First World War, with a focus on the extent to which the end of the war and the Paris peace process encouraged or disrupted the nascent international order. The focus is on western Europe, particularly France. Among the topics addressed are the relationship between gender and peace activism, international and trans-Atlantic connections, and the significance of French domestic politics to international relations. Collectively, the essays extend the ongoing debate about the success of the Treaty of Versailles: they add nuance to the debate by showing how particular issues combined both success and failure. The volume should be of interest to military, diplomatic, and international historians, with particular chapters of interest to a wider range of scholars in European history.

Médecine coloniale et santé autochtone au Saguenay et sur la Côte-Nord : de la vaccination à l’Hôpital indien de Pointe-Bleue, 1854-1894 - Arsenault, Mathieu (Revue d’études autochtones, 2022)
In tandem with the colonization of Saguenay and the North Shore, the health of Indigenous populations deteriorated during the second half of the nineteenth century. Faced with the devastation caused by a proliferation of epidemics, the Department of Indian Affairs extended its vaccination program against smallpox to the Innu. Department officials considered this an affordable, humanitarian measure. At the same time, medical practitioners on the ground saw the initiative as a means of subsidizing healthcare for the broader population. Drawing on hygienic principles concerned with the prevention of disease, in the 1870s, many of these professionals argued the overcrowded dwellings on reserves, the irresponsible nature of the Indigenous Peoples, and their nomadic tendencies rendered them dangerous threats to public health. With the support of local elected officials and the Indian agent, the State was encouraged to open an ‘Indian Hospital’ in Pointe-Bleue (1876-1894). The institution was designed to help Indigenous Peoples, often perceived as negligent, manage their own health. Yet, the presence of Innu nurses, who provided care to members of their own community, reveals a more complicated set of relations at play and allows us to question to what extent the hospital was just another colonial tool to control Indigenous bodies.
Keywords: Costa Norte; Côte-Nord; Indian hospital; Indigenous health; Innu; Innus; North Shore; Pointe-Bleue (Mashteuiatsh); Saguenay; colonial medicine; hospital indio; hôpital indien; medicina colonial; médecine coloniale; salud indígena; santé autochtone

L’éducation à la santé dans les écoles coloniales et postcoloniales d’Afrique - Ayangma Bonoho, Simplice (Revue internationale d'éducation de Sèvres, 2022)
Keywords: _AV

La singularité de l’histoire de la CTCC-CSN (1912-1960) - Rouillard, Jacques (Bulletin d'histoire politique, 2022)
Un article de la revue Bulletin d'histoire politique, diffusée par la plateforme Érudit.

La Révolution tranquille fut-elle une entreprise de masculinisation de la société québécoise ? Réflexions sur l’histoire des religieuses catholiques avant et après la laïcisation : entretien avec les historiennes Denyse Baillargeon, Aline Charles et Marie-Claude Thifault - Larochelle, Catherine (Études d'histoire religieuse, 2022)
An article from Études d'histoire religieuse, on Érudit.

L'OMS en Afrique centrale : histoire d'un colonialisme sanitaire international, 1956-2000 - Ayangma Bonoho, Simplice (Éditions Karthala, 2022)
Cet ouvrage porte sur la mise en oeuvre par l'OMS, des politiques internationales de développement sanitaire en Afrique centrale entre 1956 et 2000. Il retrace l'histoire de cette organisation internationale en Afrique et surtout, celle de la création de son bureau africain à Brazzaville (AFRO). Ce livre montre aussi comment cette trajectoire institutionnelle croise l'histoire politique de la (dé)colonisation, l'histoire de la santé publique et celle de l'humanitaire. Située au croisement de ces trois historiographies, cette réflexion tente de faire la lumière sur le rôle essentiel joué par l'OMS dans la situation sanitaire des pays de la sousrégion méso africaine, en étudiant les politiques d'hygiène, de formation des personnels de santé et l'organisation des campagnes d'éradication des maladies. En renouvelant le regard sur les politiques sanitaires internationales mises en oeuvre dans le continent africain, depuis au moins la fin de la Première Guerre mondiale, l'auteur met en valeur les ressorts d'une collaboration transnationale, non exempte de présupposés colonialistes. Cet ouvrage apparaît, dès lors, comme une référence indispensable pour réfléchir aux politiques internationales de développement sanitaire en Afrique dans leur contexte historique et politique. Simplice Ayangma Bonoho est enseignant d'histoire de l'Université de Yaoundé 1 (Cameroun) et chercheur postdoctoral Banting au Bishop's University (Canada). Il est, par ailleurs, lauréat 2022 du Prix Lombard Odier du Forum Suisse de Politique Internationale, pour l'excellence de son travail de thèse portant sur les enjeux du multilatéralisme et les nouvelles thématiques de la diplomatie multilatérale
Keywords: _AV

'World enemy bolshevism': gender, journalism & the continuities of ideological conflict in Germany, 1933-1955 - Barton, Deborah (Women's History Review, 2022)
This article uses memoirs, newspapers, and archival documents to analyse how four German women journalists became entangled in ideological conflict between Nazism, communism, and liberal democracy from the 1930s to the 1950s. Using the concept of a ‘long’ Cold War, it demonstrates how from the Third Reich to the Federal Republic of West Germany, the experiences and autobiographical writing of German women journalists who had been arrested and imprisoned by the Soviets contributed to Germany’s national identity as both a victim and a bulwark of (potential) Soviet aggression. Publishing their experiences provided these female journalists with a unique and historically specific political agency: their words echoed contemporary discourses about the supposed communist threat and how women and ideas about women were inherent in such rhetoric.
Number: 7 _eprint: https://doi.org/10.1080/09612025.2022.2070957
Keywords: Cold War; Federal Republic; Germany; Journalism; Nazism; Third Reich; autobiography; communism; democracy; gender; ideological conflict

Léon Bourgeois et Woodrow Wilson, deux conceptions de la paix - Bouchard, Carl (Léon Bourgeois et la Paix, 2022)
Le sénateur français et le président américain ont défendu deux conceptions antagonistes de la paix lors de la Conférence de Paris de 1919. Si la philosophie politique de Bourgeois est caractérisée par la grande cohérence de son projet solidariste, celle de Wilson, inspirée par le pragmatisme, est plus ambiguë. La confrontation entre les deux hommes illustre la tension qui existe, au sein des milieux internationalistes, quant à l’orientation à donner aux relations internationales après la guerre. Alors que Bourgeois défend à Paris une conception juridique, Wilson, de son côté, prétend que l’action internationale doit avant tout être guidée par la moralité et le poids de l’« opinion publique mondiale ».
https://books.openedition.org/dameae/1028

Against the Grain: Spanish Trade Policy in the Interwar Years - Betrán, Concepción; Huberman, Michael (The Journal of Economic History, 2022)
We study the effects of domestic conflict and external shocks on Spanish trade policy in the interwar period. Our account mobilizes a new granular dataset on exports and imports, and good-country level information on tariffs, trade agreements, and quotas. Into the Depression, the mainstay of policy was the tariff. The establishment of the Second Republic in 1931 was a turning point in policymaking. The new regime initiated bilateral trade negotiations. The Republic’s dilemma was to find countries willing to exchange market access. In a daunting international environment, the Spanish case offers a poignant reminder of the perils of going against the grain.

Parler de l'Amérique dans les écoles de France et de Belgique (1915-1919) - Bouchard, Carl (Les États-Unis en France et en Europe, 1917-1920: circulation et diffusion des idées et des savoirs, 2022)

Woodrow Wilson et l’Europe centrale et orientale - Bouchard, Carl; Dallaire, Frédéric (reCHERches, Culture et histoire dans l'espace roman, 2022)
Le président Wilson a fait de l’autodétermination une clé de voûte du nouvel ordre mondial, mais le concept est appliqué de façon arbitraire lors des négociations de paix de 1919. L’Europe centrale et orientale, dont Wilson avait une connaissance très limitée, constitue à cet égard un laboratoire. Cet article s’intéresse à la formulation de la politique américaine dans cet espace à travers les travaux de l’Inquiry, le groupe d’experts chargé de penser l’après-guerre, et examine les lettres des groupes et des individus qui ont tenté d’influencer la position du président américain sur cette question.
ISBN: 9791034401185 Number: 29
Keywords: Europe centrale; Europe orientale; The Inquiry; Woodrow Wilson; autodétermination; paix de 1919; politique américaine

Beyond the Great War: Making Peace in a Disordered World - Bouchard, Carl; Ingram, Norman (University of Toronto Press, 2022)
Following the end of the First World War, a new world order emerged from the Paris Peace Conference of 1919. It was an order riddled with contradictions and problems that were only finally resolved after the Second World War. Beyond the Great War brings together a group of both well-established and younger historians who share a rejection of the dominant view of the peace process that ended the First World War. The book expands beyond the traditional focus on diplomatic and high political history to question the assumption that the Paris Peace Treaties were the progenitors of a new world order. Extending the ongoing debate about the success of the Treaty of Versailles and surrounding events, this collection approaches the heritage of the Great War through a variety of lenses: gender, race, the high politics of diplomacy, the peace movement, provision for veterans, international science, socialism, and the way the war ended. Collectively, contributors argue that the treaties were at best a mitigated success, and that the "brave new world" of 1919 cannot be separated from the Great War that preceded it.

Quand l'histoire urbaine et l'histoire environnementale se rencontrent: un survol des travaux récents au Québec - Dagenais, Michèle (Urban History Review / Revue d'histoire urbaine, 2022)
L’intégration des perspectives d’histoire environnementale en histoire des villes a contribué à renouveler le champ de l’histoire urbaine. À travers l’examen des travaux réalisés à partir des années 2000, l’article montre les apports de l’histoire environnementale à l’histoire urbaine, en particulier au Québec.

Brébeuf, Jean de (Échon en huron) (1539-1649) - Deslandres, Dominique (Les Jésuites: histoire et dictionnaire, 2022)

Garnier, Charles (Ouracha en huron) (1605-1649) - Deslandres, Dominique (Les Jésuites: histoire et dictionnaire, 2022)

Intimes ennemis : l’asservissement des enfants pendant le Régime français - Deslandres, Dominique (Les Cahiers des dix, 2022)
Les archives judiciaires, notariales et paroissiales révèlent l’ampleur et la pérennité de l’esclavage infantile en Nouvelle-France. En témoignent les traces de vies d’enfants esclaves, en majorité autochtones, qui apparaissent constamment au fil des documents du xvie au xviiie siècle. Comment expliquer cet attrait quasi pédophile pour des esclaves âgés de moins de 12 ans ? À quoi les maîtres peuvent-ils bien employer des esclaves si jeunes ? Qui les « gère » au quotidien ? Quelles sont la place et les fonctions de ces jeunes asservis dans les familles esclavagistes ? Et enfin, comment cette violence répétée de l’asservissement des enfants a-t-elle été justifiée ? Par toutes ces questions qu’il soulève, ce véritable angle mort de la recherche qu’est l’esclavage infantile, éclaire d’une lumière crue, d’une part, les rapports de pouvoir à l’oeuvre dans la société coloniale et patriarcale, dont les fondements hiérarchiques sont irradiés par un faisceau de servitudes et, d’autre part, l’histoire socio-économique de la Nouvelle- France, sachant que, sous le Régime français, la majorité des foyers, qui aujourd’hui posséderait sa voiture, possédait au moins un ou une esclave.
Keywords: 16th to 18th centuries; New France; Nouvelle-France; afrodescendance; afrodescendant; autochtones; children; enfants; esclavage; esclaves; indigenous; slavery; slaves; xvie; xviie et xviiie siècles

Jogues, Isaac (Ondessonk en huron) (1607-1646) - Deslandres, Dominique (Les Jésuites: histoire et dictionnaire, 2022)

Rale (Râle, Rasle, Rasles), Sébastien (1652-1724) - Deslandres, Dominique (Les Jésuites: histoire et dictionnaire, 2022)

Disputing New France: companies, law, and sovereignty in the French Atlantic, 1598-1663 - Dewar, Helen (McGill-Queen's University Press, 2022)
"From the early sixteenth century, thousands of fishermen-traders from Basque, Breton, and Norman ports crossed the Atlantic each year to engage in fishing, whaling, and fur trading, which they regarded as their customary right. In the seventeenth century these rights were challenged as France sought to establish an imperial presence in North America, granting trading privileges to certain individuals and companies to enforce its territorial and maritime claims. Bitter conflicts ensued, precipitating more than two dozen lawsuits in French courts over powers and privileges in New France. In Disputing New France Helen Dewar demonstrates that empire formation in New France and state formation in France were mutually constitutive. Through its exploration of legal suits among privileged trading companies, independent traders, viceroys, and missionaries, this book foregrounds the integral role of French courts in the historical construction of authority in New France and the fluid nature of legal, political, and commercial authority in France itself. State and empire formation converged in the struggle over sea power: control over New France was a means to consolidate maritime authority at home and supervise major Atlantic trade routes. The colony also became part of international experimentations with the chartered company, an innovative Dutch and English instrument adapted by the French to realize particular strategic, political, and maritime objectives. Tracing the developing tools of governance, privilege granting, and capital formation in New France, Disputing New France offers a novel conception of empire–one that is messy and contingent, responding to pressures from within and without, and deeply rooted in metropolitan affairs."– Provided by publisher.
Keywords: =CL

Statut corporatif et responsabilité personnelle dans la liquidation des dettes de la Compagnie de la Nouvelle-France - Dewar, Helen (Revue d’histoire de l’Amérique française, 2022)
The historiography on the Compagnie de la Nouvelle-France (CNF) focuses primarily on its role in the colonization of New France. By examining its form, this article resituates the CNF in the larger history of European experimentations with the joint-stock company. The liquidation of the company’s debts in the 1630s and 1640s forced associates, directors, and jurists to articulate their understanding of who was liable for the enterprise’s financial health. Evaluating the legal and moral arguments of the parties concerned, this article argues that the complexity of the liability of associates and directors resulted from the intersection of the corporate, monarchical and commercial worlds.
Number: 4

Red Vienna: A Social Housing Experiment, 1923–1933 - Holzner, Mario; Huberman, Michael (The Journal of Interdisciplinary History, 2022)
The moderating effects of World War I on wealth and income inequality varied with the belligerents. In Austria, the state embraced austerity measures to eliminate hyperinflation and respect commitments to the League of Nations. To fill the void, the Social Democratic Workers’ Party (sdap) turned to its political stronghold in Vienna to advance its agenda of social spending and progressive taxation—Red Vienna’s signature program. The use of an electoral-cycle model finds that the construction of new buildings increased the party’s share of votes in municipal elections. The program mobilized support of young families in search of affordable and quality housing, also attracting the endorsement of the middle classes and elites, despite the higher tax burden imposed on them. The physical attributes of the new buildings and related investments, such as in schools, hospitals, and city infrastructure, benefited the entire population of Vienna.
Number: 1

La COFACE entre boom et décélération économique (1966-1985) - Saul, Samir (Explorer les archives et écrire l'Histoire. Autour de Roger Nougaret, 2022)

'A female voice is instrumental': gender, propaganda, and coerced labor on the Eastern Front, 1943-1945 - Barton, Deborah (Labor History, 2022)
This article examines the role of local, female propagandists utilized by the German army on the Eastern Front during WWII. Although the work they undertook aligned with postwar notions of collaboration, the propagandists’ experiences at the hands of the Wehrmacht, in a context of a violent war and repressive occupation, constitutes coerced labour in multiple forms. Regardless of the women’s motivations for working for the Wehrmacht, they entered a relationship of domination and dependence with the occupation force. While female propagandists numbered far fewer than their male counterparts, they held a particular importance for German high command who believed that their “feminine” traits, such as empathy and charm, helped the Wehrmacht influence and control the largely female civilian population. At the same time, their work on the frontlines encouraging Red Army soldiers to defect crossed traditional gender boundaries. In this task too, the women were valued for their gender with German authorities believing that Soviet soldiers, largely deprived of female contact, would be particularly receptive to the charm of a woman’s voice. Such coerced labor on behalf of the Wehrmacht rendered these women vulnerable not only to German violence, but also to Soviet accusations of collaboration and its associated reprisals.
Number: 3 _eprint: https://doi.org/10.1080/0023656X.2022.2146077
Keywords: Eastern front; Propaganda; Wehrmacht; coerced labor; gender; war

Sommes-nous des porcs ou des chevaux? Familiarité et distinction entre humains et animaux dans les derniers siècles du Moyen Âge - Genequand, Philippe (Les animaux... l'histoire continue: rencontres pluridisciplinaires autour de Robert Delort, 2022)